2017
DOI: 10.1111/jgh.13802
|View full text |Cite
|
Sign up to set email alerts
|

Serum Wisteria floribunda agglutinin‐positive Mac‐2‐binding protein levels and liver fibrosis: A meta‐analysis

Abstract: These results suggest that serum WFA -M2BP is a reliable predictor for liver fibrosis staging and a good substitute for liver biopsy. It is also useful for predicting both hepatocellular carcinoma development and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
0
38
1
2
Order By: Relevance
“…M2BP has been identified as one of the major glycoproteins secreted from injured hepatocytes. WFA + -M2BP is a glycan structure isoform of M2BP and can be measured with a rapid, simple glycan-based immunoassay to quantify liver fibrosis in different chronic liver diseases [ 11 , 17 , 18 ]. The first study to assess the performance of WFA + -M2BP in predicting disease severity in NAFLD was done by Abe et al and included 289 Japanese patients with biopsy-proven disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M2BP has been identified as one of the major glycoproteins secreted from injured hepatocytes. WFA + -M2BP is a glycan structure isoform of M2BP and can be measured with a rapid, simple glycan-based immunoassay to quantify liver fibrosis in different chronic liver diseases [ 11 , 17 , 18 ]. The first study to assess the performance of WFA + -M2BP in predicting disease severity in NAFLD was done by Abe et al and included 289 Japanese patients with biopsy-proven disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that Wisteria floribunda agglutinin-positive Mac-2 binding protein (WFA + -M2BP) is a promising biomarker in predicting the severity of liver fibrosis in different chronic liver diseases [ 11 ]. Mac-2 (galectin-3) binding protein (M2BP) is a glycoprotein that is almost undetectable in normal liver but becomes easily detected in patients with hepatocyte injury as liver fibrosis progresses.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the serum WFA + ‐M2BP level is now covered by the health insurance system in Japan. A recent meta‐analysis showed that the serum level of WFA + ‐M2BP is useful for detecting advanced fibrosis or as well as for predicting HCC development in patients with chronic liver disease, including hepatitis B virus, hepatitis C virus, and NAFLD …”
Section: Discussionmentioning
confidence: 99%
“…In the past, numerous noninvasive panels of tests have been developed for the staging of liver fibrosis, including a combination of clinica and routine laboratory parameters, as well as specialized tests involving direct markers of fibrosis. Recently, Wisteria floribunda agglutinin‐positive Mac‐2‐binding protein (WFA + ‐M2BP) was discovered as a novel serum glycomarker for marker of liver fibrosis from glycoproteomic biomarker screening studies …”
Section: Introductionmentioning
confidence: 99%
“…Fibrosis markers also have been extensively examined, including hyaluronic acid, type IV collagen 7S, procollagen III peptide and Wisteria floribunda agglutinin-positive Mac-2-binding protein (WFA+ -M2BP). A recent meta-analysis showed that measurement of the serum level of WFA+ -M2BP, which is now covered by the health insurance system in Japan, is useful for detecting severe fibrosis or predicting HCC development in patients with chronic liver disease [ 28 ]. WFA+ -M2BP is also of clinical use for assessing liver fibrosis in patients with NAFLD [ 29 , 30 ].…”
Section: Biomarkers and Scoring Systemsmentioning
confidence: 99%